Microencapsulamento por gelificação iônica de abóbora de leite (Cucurbita moschata D.) com elevado teor de carotenoides e aplicação em iogurte - Pinheiro, Rubimara Cristina (2019)
The pumpkin has been consumed for centuries in human food and has great economic and social relevance in Brazil, its constituents pulp, among other micronutrients, are carotenoids, but its pulp and seeds have a low degree of industrialization and few products of this raw material are offered. In addition, the biofortification process of vegetables, especially pumpkin, may allow an increase of carotenoids and reduce vitamin A deficiency in children. The objective of this research was to evaluate the physical, chemical-physical and chemical characteristics of carotenoids enriched pumpkin (Cucurbita moschata D), to determine in vitro antioxidant capacity, besides sensory evaluation of the effect in incorporation enriched pumpkin microcapsules on flavor of natural yoghurt. Conventional and enriched with carotenoids (AEC) pumpkins were acquired from Embrapa Tabuleiros Costeiros/SE plant breeding project, physical-chemical characteristics and centesimal composition were determined, such as total carotenoids and phenolic compounds were quantified. Antioxidant activity was evaluated in different in vitro methods (DPPH, ABTS and FRAP). The AEC microcapsules were produced and added to a commercial natural yoghurt in a proportion of 5 and 10%. The two products were sensory evaluated employing an acceptance test with a 9-point hedonic scale with children, that were appointed to evaluate the sensory attribute of ‘‘flavour’’. pH, titratable acidity and total soluble solids have not significant differences (p> 0.05), showing that both samples, conventional and AEC, with same stage of maturation. For the parameters a * and b * of the color, the AEC was higher (p <0.05), it’s justified by high total carotenoid contents (322.67 ± 6.21 μg / g) compared as conventional pumpkin (173.87 ± 3.60 μg/g). There was an increase in total phenolic compound content of AEC sample (p <0.05), total phenolic compounds and carotenoids are possibly correlated with expressive antioxidant capacity. In sensory evaluation, Yogurt containing AEC microcapsules was well accepted by children, mainly, formulation with 10% microcapsules, the scores were 7.2.